Creativity Without Borders: Integrating Heart and Soul Into Caregiver Training - Fernandes, Ritabelle (Journal of pain and symptom management, 2025)
1. Participants will be able to recognize the connection between art and science, how everything connects to everything else. 2. Participants will be able to understand the need for health professionals developing caregiver training to add creativity to didactics. This presentation will explain the family caregiver curriculum conducted in American Samoa in partnership with the Catholic Diocese as part of a 5-year ANA grant. A creativity workshop to meet the emotional needs of caregivers and ease the burden of caregiving. We will share the video and booklet that were developed by the caregivers in Samoa. The ‘Tausi Feagaiga (Covenant Keeper) project was a partnership between community organization Pacific Youth and Community Development, faith-based organization Roman Catholic Diocese of Samoa-Pago Pago, and higher learning institute University of Hawaii John A. Burns School of Medicine.(1) There was a need for caregivers to express their stress and burnout. The goal of the creativity workshop was to facilitate a creativity and self-expression where participants wrote and performed short prose and poetry pieces. Tausi Feagaiga was developed based on an existing Family Caregiver Certificate that had been developed by Pacific Islands Geriatric Education Center. (2) In years 4 and 5 of ‘Tausi Feagaiga, a caregiving creativity workshop was added to meet the emotional needs of caregivers. The workshop was designed to incorporate local culture of song, dance, poems, drawing, and drama. Caregivers were encouraged to imagine, read, dance, and speak in a safe nurturing environment. The facilitator encouraged them to speak and write using all their senses, visualizing deeply. Some of the exercises included: What does fear smell like? What does inspiration taste like? Gather a poem using objects from nature. Results: Over the course of 5 years from 2016 – 2020, 125 caregivers were trained in family caregiving. The product of the caregiver creativity workshop, short story poems and songs were developed into a booklet in year 4 and a video in year 5. (3) Fa'a Samoa, or the Samoan way supports traditional values of tausi matua encouraging caring for your elders. There is a certain kind of alchemy in writing poetry. Metaphors bring healing by helping people to listen to their inner voice that guides them to share stories only they can tell. When art and science connect, the heart and soul releases creativity that can bring about transformative healing. 1. Fernandes R, McCutchan K, Allen N. ‘Tausi Feagaiga: impacting health care in an island nation. Asia Pac J Public Health 2021;33(6-7):792-793. 2. Fernandes R, You P, Reichhardt M, et al. Building capacity for caregiver education in Yap, Micronesia. Hawaii J Health Soc Welf. 2000;79(8):78-81. 3. Faraway is Close. Accessed November 14, 2020. https://www.farawayisclose.com